1991
DOI: 10.1002/jctb.280510103
|View full text |Cite
|
Sign up to set email alerts
|

Purification and kinetics of penicillin G acylase from a mutant strain of escherichia coli ATCC 11105

Abstract: A mutant strain with high penicillin G acylase activity was derived from Escherichia coli ATCC 11105 by chemical mutagenesis, using N‐methyl‐N′‐nitro‐N‐nitrosoguanidine. Penicillin acylase was extracted from the mutant strain and highly purified by DEAE‐cellulose and hydroxyapatite column chromatography followed by preliminary precipitation steps. Vm and Km values of the enzyme (specific activity: 24·81 U mg−1, protein concentration: 0.56 mg cm−3) were found to be 22.73 U cm−3 mm−1 and 3.18 mmold m−3 penicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 16 publications
2
4
1
2
Order By: Relevance
“…It can be also concluded that 6-APA is a noncompetitive and PAA is a competitive inhibitor. This is in agreement with the results previously reported [12,14,15,25,26]. Jianguo et al [25] determined inhibition constants as K iA = 0.009 M and K iB = 0.013 M for PGA immobilized on poly(vinyl acetate-co-divinyl benzene) beads.…”
Section: Effect Of 6-apa and Paa On The Free And Immobilized Pgasupporting
confidence: 90%
See 2 more Smart Citations
“…It can be also concluded that 6-APA is a noncompetitive and PAA is a competitive inhibitor. This is in agreement with the results previously reported [12,14,15,25,26]. Jianguo et al [25] determined inhibition constants as K iA = 0.009 M and K iB = 0.013 M for PGA immobilized on poly(vinyl acetate-co-divinyl benzene) beads.…”
Section: Effect Of 6-apa and Paa On The Free And Immobilized Pgasupporting
confidence: 90%
“…Jianguo et al [25] reported a K M value of 0.033 M, which is almost the same as the K M value obtained in the present study showing the same affinities for the substrate of the immobilized enzymes. Likewise, some of the previously reported values for K M of the PGA immobilized on different carriers were 4.17 mM [12], 11.36 mM [14], and 3.18 mM [15]. These values are lower than the obtained K M value (32.6 mM) probably due to higher film diffusion resistance to the substrate transport near the chitosan microbeads.…”
Section: Reaction Kineticscontrasting
confidence: 62%
See 1 more Smart Citation
“…Takođe je pokazano i da i slobodnu i imobilisanu PAC inhibira supstrat u višku i oba proizvoda reakcije, pri čemu je 6-APA nekompetitivni, a PAA je kompetitivni inhibitor. Ovi rezultati se slažu sa rezultatima objavljenim u literaturi [29,50,244,246,247]. Za imobilisanu PAC na poli(vinil acetat-ko-diviil benzen) česticama dobijene su vrednosti za K iA i K iB od 0,009 mmol/cm 3 i 0,013 mmol/ cm 3 , redom [246].…”
Section: Ispitivanje Stabilnosti Imobilisanog Enzima Nakon Višekratneunclassified
“…Ove vrednosti su niže nego K iA i K iB vrednosti dobijene u ovom radu, stoga, u ovom slučaju uticaj inhibitora na naš biokatalizator je manji. Takođe, u literaturi su objavljene i vrednosti K iA i K iB za PAC imobilisanu na različite nosače: 100,7 mmol/dm 3 i 68,6 mmol/dm 3 [247], odnosno 76,1 mmol/dm 3 i 90 mmol/dm 3 , redom [50]. Ove vrednosti su veće od K iA i K iB vrednosti koje su dobijene u ovom radu, pa može da se zaključi da je uticaj inhibitora (6-APA i PAA) na naš biokatalizator veći.…”
Section: Ispitivanje Stabilnosti Imobilisanog Enzima Nakon Višekratneunclassified